Still my forever : a novel - Sawyer, Kim Vogel (WaterBrook, 2022)
"A struggling composer senses a chance to get back on track and rekindle an old flame-even if it means hiding the truth of his failures-in this charming romance inspired by a historical figure from the bestselling author of Freedom's Song"--